METODE PENGAJARAN TAHFIDZ AL-QUR’AN PADA ANAK TUNARUNGU DI SEKOLAH MENENGAH PERTAMA LUAR BIASA YAYASAN ASUHAN ANAK TUNA SURAKARTA - Hasram Efendi; Nurul Latifatul Inayati (Universitas Muhammadiyah Surakarta, 2020)
The deaf children who are born with special needs have the opportunities as same as normal children, including the teaching of Tahfidz Al-Qur'an. If the normal children can memorize the Qur'an until the final stages of 30 juz, then actually children with the disability also have the opportunity as same as them. Even though their success is also very much influenced by the method of education they receive. This study discusses the method of teaching Tahfidz Al-Qur'an for children with hearing impairment and how to evaluate the learning outcomes of students with hearing impairment in memorizing the Al-Qur'an with these methods at the SMPLB Foundation for the Tuna Children's Care Foundation Surakarta.This research is qualitative research by taking place and subject in the special education school of Yayasan Asuhan Anak Tuna in Surakarta. The method of collecting data is an interview, observation, and documentation. The data is analyzed with a deductive method. To ensure the validity of the data that has been obtained, this is done by conducting technical triangulation, sources, and time.The results show: (1) teachers using various creativities and various methods make students can memorize letters in the Qur'an. The teacher applies at least three methods: Lecture, Drill, and Assignment methods. (2) evaluation is held on each learning end or daily test, the teacher always corrects how much the capacity of memory from each student is. Formative evaluation tests, which prioritize student practice in depositing memorization of the verses of the Qur'an that have been given by the teacher. The evaluation is carried out on each schedule of Islamic education that it takes place with starting with a muroja’ah together, then those students are invited to submit memorization following what was assigned. This assessment adds the value of students in Islamic Education.